Spiritualitas dan Transformasi - Daeli, Onesius O. (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2018)
Spirituality is a virtue of being men and women. It is a significant sign to distinguish human from nonhuman. In this sense, spirituality is a particular drive to motivate people to enter their true self and to explore their inner talents. A person needs spirituality in order to be considered as an authentic person, because spirituality is basically an integral part of his or her existence. Spirituality enables people to explore, develop, and transform their talents to be an excellent contribution for humanity. It is not only associated with humans’ internal desires, but also something that leads them to use, develop, and optimize various other materials and cultures that could be treasured around them. Spirituality is a power to create a better life. Although spirituality is varied and at the same time unique because it is fundamentally and intrinsically local and localized, one must understand that spirituality is always an identity in action. It shapes and transforms human’s life as well as the world.